LAMBATNYA PENANGANAN PERKARA TINDAK PIDANA KARENA TIDAK OPTIMALNYA KOORDINASI DALAM TAHAP PRAPENUNTUTAN (URGENSI PERWUJUDAN SISTEM JAKSA ZONA) - Nurul Dewinta; Haeranah Haeranah; Nur Azisa (Universitas Widya Gama Malang, 2019)
This study purpose to determine: the implementation of coordination between investigators and public prosecutors at the pre-prosecution stage, obstacles that arise in the implementation of coordination between investigators and public prosecutors as well as efforts made to maximize the coordination function at the pre-prosecution This research is empirical normative research. In order to obtain data relevant to the needs of this research, the author conducted a study at the Kotamobagu District Prosecutor's Office and Kotamobagu Resort Police. The results of the study show that (1) In handling a criminal case, the party responsible for law enforcement should establish a good coordination so that the duration of the case handling process does not occur which results in a fast, simple and low cost judicial principle. However, the coordination carried out by investigators at the Kotamobagu Resort Police and the public prosecutor at the Kotamobagu District Attorney's Office at the pre-prosecution stage has not been carried out to the maximum. (2) Constraints that arise in coordinating and the efforts made to maximize the coordination function at the pre-prosecution stage based on the Kotamobagu District Prosecutor's case study and Kotamobagu Resort Police. 3) the community uses the law as a tool to achieve personal goals, for example, get material benefits so that the efforts taken are to carry out legal counseling to the community.